Portomesenteric venous thrombosis as a rare complication of acute appendicitis in pediatric patient: a case presentation and literature review - Tsz Yan Nancy Lai; Judy WS Hung; Michael WY Leung (SpringerOpen, 2022)
Abstract Background Appendicitis is one of the most common paediatric surgical emergencies, however complication with acute portomesenteric venous thrombosis is rare. Our aim is to report a case in our locality and review the clinical features and management of such rare complication. Case presentation A 12-year-old boy presented with a 5-day history of fever, periumbilical and right lower quadrant abdominal pain, blood-stained diarrhea and vomiting. Physical examination showed tenderness and guarding over right upper quadrant. Laboratory tests showed elevated inflammatory markers and deranged liver function. Contrast computed tomography scan showed acute appendicitis and superior mesenteric vein thrombosis. Our patient was treated with laparoscopic appendicectomy, antibiotics, and anticoagulant, with gradual improvement of thrombus observed. Conclusion Our patient and seventeen pediatric case reports regarding the condition since 1990 were included. Atypical presenting symptoms were noted, including RUQ pain (n = 10, 56%), diarrhea (n = 8, 44%), fever (n = 16, 89%), deranged liver function (n = 13, 72%). Patient presenting with RLQ pain were only seen in 22% (n = 4). Diagnosis was made by USG (n = 1, 5%) and computer tomography (n = 15, 83%). Surgical intervention includes early (n = 9, 50%) or interval (n = 4, 22%) laparoscopic or open appendicectomy, laparotomy etc. The most common causative organisms were Escherichiae coli and Bacteroides fragilis. Anticoagulant use and its duration remained controversial. Anticoagulant was used in 14 patients with a mean treatment duration of 7 months, while 4 cases reporting resolution of thrombus without anticoagulant use. A high index of suspicion is needed to diagnose patient with acute appendicitis complicated by portomesenteric thrombosis.